Pengembangan Media Pembelajaran Berbantuan Podcast Edukatif Dengan Pendekatan OBE Untuk Meningkatkan Kemampuan Berpikir Kritis (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This research aimed to develop and test the effectiveness of educational podcast-assisted learning media with an Outcome Based Education (OBE) approach in improving students' critical thinking skills in the Neoclassical Economic Thought course. The method employed was Research and Development (R&D) through ten steps according to Sugiyono (2017), involving 32 Economic Education students at Universitas Negeri Medan as subjects. A needs analysis identified key student challenges: difficulty understanding abstract material (mean X1 = 3.17), obstacles due to difficult terminology (mean X3 = 3.17), and the need for flexible media. The educational podcast was developed to offer a communicative audio format capable of simplifying abstract concepts. Feasibility testing by expert validators showed the medium was Very Feasible with an overall average score of 81.1%. Following the intervention using the podcast media, a significant increase in students' critical thinking skills occurred (average score increased from 55.6 on the pretest to 92.1 on the posttest). The effectiveness analysis using the N-Gain test yielded an average value of 0.80, which is classified as High. It is concluded that the OBE-based educational podcast media proved to be Feasible and Effective in enhancing students' critical thinking skills, aligning with the 21 century demands for student-centered and results-oriented learning.
Keywords: Educational Podcast, Outcome Based Education (OBE), Critical Thinking, Neoclassical Economic Thought, R&D.